Electrohydrogenation of Carbon Dioxide using a Ternary Pd/Cu2O–Cu Catalyst. Issue 19 (3rd September 2019) - Li, Jing; Guo, Si‐Xuan; Li, Feng; Li, Fengwang; Zhang, Xiaolong; Ma, Jiantai; MacFarlane, Douglas R.; Bond, Alan M.; Zhang, Jie
Abstract: A simple one‐pot method has been developed to synthesize a palladium/cuprous oxide‐copper (Pd/Cu2 O–Cu) material with a well‐defined structure, by modification of Cu2 O–Cu with Pd through a galvanic replacement reaction. Compared with the well‐known copper/cuprous oxide (Cu/Cu2 O) catalysts, the Pd/Cu2 O–Cu material can catalyze the electroreduction of CO2 into C1 products with much higher faradaic efficiencies at lower overpotentials in a CO2 ‐saturated 0.5 m NaHCO3 solution. In particular, the highest faradaic efficiencies of 92 % for formate and 30 % for methane were achieved at −0.25 and −0.65 V (vs. the reversible hydrogen electrode), respectively. The improvement is suggested to be the result of a synergistic effect between PdH and the catalytically active copper sites during electrochemical CO2 reduction. Abstract : Turning CO2 into C1 : A simple one‐pot method has been developed to synthesize a Pd/Cu2 O–Cu material with a well‐defined structure, by modification of Cu2 O–Cu with Pd through a galvanic replacement reaction. Compared with the well‐known Cu/Cu2 O catalysts, the newly synthesized Pd/Cu2 O–Cu material can catalyze the electroreduction of CO2 into C1 products with much higher faradaic efficiencies at lower overpotentials in a CO2 ‐saturated 0.5 m NaHCO3 solution.